Feminist Collections, v.7, no.2 (winter 1986) - (:unkn) unknown (My University, 1986)
Subtitle: A Quarterly of Women's Studies Resources. 34p.
FROM THE EDITORS: Feminist Collections now available on tape. ARCHIVES: Black women in La Crosse, by Bruce L. Mouser. FEMINIST VISIONS: Media for fighting the double discrimination of ableism and sexism, by Elizabeth Ellsworth. NEWS FROM UW-MADISON: By Ruth Bleier, Diane Kravetz, and Suzanne Pingree. NOTE TO SUBSCRIBERS: Recent changes in New Books on Women & Feminism. NEW REFERENCE WORKS IN WOMEN'S STUDIES: New sources on women composers; French feminist criticism; American women managers and administrators; women writers; sexual harassment; women artists; sexuality; the status of women worldwide; films for, by, and about women; and women and law. PERIODICAL NOTES: New periodicals on: older women; Minnesota women; women's poetry, stories, and artwork. Special issues on: Nairobi, '85; women in migration; feminist social philosophy; women and the family; the Women's International League for Peace and Freedom; refugee women; sex and gender. Ceased publication: Catalyst Media Review; Lammas Little Review. ITEMS OF NOTE: The National Women's History Project 1986 catalog; 1985 List of Alternative and Radical Publications; proceedings of a 1984 conference on mentoring and women; and working papers from the Center for Twentieth Century Studies, UW-Milwaukee. WISCONSIN BIBLIOGRAPHIES IN WOMEN'S STUDIES: New bibliographies on films and videotapes about women, self-help publishing in the '80s, and feminist Shakespeare criticism. BOOK REVIEWS: Nineteenth-century communities of single wmen in Britain and the U.S., by Margo A. Conk. Clerical work and clerical workers, by Cynthia Costello. Selected new resources for integrating women's studies into the curriculum, by Betty Schmitz.
Keywords: Women's Studies; Gender; Feminism; Library Resources; Reviews